PENGARUH KEJELASAN TUJUAN, DUKUNGAN ATASAN DAN PELATIHAN TERHADAP KEGUNAAN SISTEM AKUNTANSI KEUANGAN DAERAH DENGAN KONFLIK KOGNITIF DAN KONFLIK AFEKTIF SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Satuan Kerja Perangkat Daerah Kabupaten Indragiri Hili - Sari, Nanda Rakhmata; Taufik, Taufeni; Hanif, Rheny Afriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
the research aims to analyze of influencing goal clarity, support superior and training to the use of local government financial accounting system with conflict cognitive and conflict affective as intervening variable. Object of this research is department of SKPD Indragiri Hilir. There are one hundred twenty eight questionnaires were sent, and one hundred twenty eight questionnaires are returned. The data are analyzed by structural equation model and using PLS (partial least square) program. The results of this research showed goal clarity has an effect to the use of local government financial accounting system with direct effect 0,000 significance, support superior has an effect to the use of local government financial accounting system with direct effect 0,010 significance, training has an effect to the use of local government financial accounting system with direct effect 0,000 significance, conflict cognitive has an effect to the use of local government financial accounting system with direct effect 0,000 significance and conflict affect has an effect to the use of local government financial accounting system with 0,020 significance. Each independent variables, gives the strong influence to dependent variable, it means independents variables could explain dependent variable well. While the remaining influenced by other variables not included in the structural equation model were not included in this study. All variables also have strong relation with variable dependents in this research.Keywords: goal clarity, support superior, training, conflict cognitive, conflict affective and financial accounting system